ANALISIS IMPLEMENTASI PRINSIP AKUNTABILITAS DAN TRANSPARANSI PADA LEMBAGA SWADAYA MASYARAKAT - Agata Rangga Pamungkas; Bambang Hariadi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
This research was motivated by the importance of Non Governmental Organization (NGO) to improve accountability and transparency as an effort to gain public confidence. There were six aspects of the assessment criteria, namely the formulation of the vision and mission, administration management, organization management, program management, financial management, and community recognition. This study would evaluate and analyze six major aspects that influence to the determination of the accountability and transparency quality of the organization. In addition, researcher also attempted to analyze the advantages and disadvantages of organization governance that had been applied by the organization. In order to researcher could evaluate the application of six aspects, researcher used a descriptive qualitative research method. Results of this study concluded that the application of the accountability and transparency principles had done well, but still needed any reformation in recruitment of internship or contract staffs. Self-supporting public institutions also needed to survey the organization performance according to public perception. Keywords: Accountability, Transparency, Non Government Organization